Quantitative Paleozoology - Steve Wolverton (Ethnobiology Letters, 2010)
Review of Quantitative Paleozoology. R. Lee Lyman. 2008. Cambridge University Press, Cambridge. Pp. 348, black-and-white illustrations. $29.34 (paper). ISBN 9780521715362.